Model Development Of Cooperative Learning in Improving The Quality of Student Learning in Islamic Religious Education Subject - Rulitawati Rulitawati; Ayu Munawarah (IJER (Indonesian Journal of Educational Research), 2018)
This research is a developmental research which aims to find out the learning model to improve students learning outcomes of islamic learning in MadrasahAliyah Negeri 2 Palembang, South Sumatera. Focus in this study was the subject of jurisprudence. This study offers to reconstruct islamic learning (PAI) iin the school which was originally put on the lecture method into cooperative learning methods. So that students do not feel bored and get better learning outcomes. The modal applied in this study is STAD type. The analytical method used is descriptive qualitative and quantitative analysis. Form pretest analysis, it can be concluded that there is no difference in significance between pre-test cognitive learning outcomes of experimental class students and control class students. Whereas, post-test cognitive learning outcomes of students in the experimental class and control class students obtaint tcount = 2.560 (Equal variances assumed). While the value of ttable = 2,292, means tcount > ttable (2,560 > 2,292) the Ho rejected. So, it can be concluded that there are differences between post-test cognitive learning outcomes of experimental class students and control class students.